A pilot trial of In vivo NRT sampling to increase medication adherence in community corrections smokers. (April 2017) - Cropsey, Karen L.; Hendricks, Peter S.; Schiavon, Samantha; Sellers, Aaron; Froelich, Morgan; Shelton, Richard C.; Carpenter, Matthew J.
Abstract: Background: Individuals in the criminal justice system demonstrate high rates of cigarette use (70–80%) and low adherence to smoking cessation medication. Educational approaches have not been shown to promote adherence or cessation, though medication sampling has boosted both use and cessation. The objective of the present study was to determine whether In vivo nicotine replacement therapy (NRT) sampling approach increases NRT adherence among criminal justice smokers during a subsequent quit attempt. Methods: We conducted a pilot study with 43 community corrections smokers randomized to a 4-session (one 30-min session per week) precessation intervention of either In vivo NRT sampling (Session 1: patch; Session 2: gum; Session 3: combination NRT (cNRT); Session 4: review) vs. 4 time-matched sessions of standard smoking cessation with cNRT started after Session 1. Both groups received an additional 8 weeks of cNRT following the four intervention sessions. Results: During the in vivo administration of NRT, total withdrawal and craving severity significantly decreased from pre- to post-session compared to Control participants. In vivo participants evinced greater patch use at Session 4 and greater gum use through Week 8 relative to Controls. Discussion: In vivo NRT sampling may increase NRT adherence relative to standard counseling sessions among criminal justice smokers. A larger trial of this novel intervention appears to be warranted. Highlights: Novel behavioral intervention designed to improve smoking cessation NRT adherence. In vivo intervention group evinced greater patch use and gum use. Intervention group reported decreased withdrawal and craving severity. In vivo NRT sampling may increase NRT adherence relative to standard counseling.